2018
DOI: 10.1093/mmy/myy004
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia pachydermatis up-regulates AhR related CYP1A1 gene and epidermal barrier markers in human keratinocytes

Abstract: Cytochrome P450 CYP1A1 and CYP1B1 enzymes are regulated by the aryl hydrocarbon receptor (AhR), a transcription factor activated by a variety of ligands among which Malassezia metabolites. In this study, we analyzed the modulation of CYP1A1, CYP1B1, and AhR in human keratinocytes infected with different strains of Malassezia pachydermatis, as well as the upregulation of some genes involved in the epidermal homeostasis. We demonstrated that all the strains induced AhR activation and its nuclear translocation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Malassezia yeast represent one of the most well‐known microbial genera of the normal skin flora. Several Malassezia metabolites, particularly indirubin and tryptanthrin, are reportedly ligands of the AhR, which stimulates NHKCs to increase the production of CYP1A1 as well as proinflammatory and Th2 cytokines . In addition, Malassezia species indirectly increase MMP activity .…”
Section: Resultsmentioning
confidence: 99%
“…Malassezia yeast represent one of the most well‐known microbial genera of the normal skin flora. Several Malassezia metabolites, particularly indirubin and tryptanthrin, are reportedly ligands of the AhR, which stimulates NHKCs to increase the production of CYP1A1 as well as proinflammatory and Th2 cytokines . In addition, Malassezia species indirectly increase MMP activity .…”
Section: Resultsmentioning
confidence: 99%
“…Under physiological conditions, endogenous AHR ligands, such as tryptophan photoproducts [15,26,83] and microbial bioproducts [17,19,87], may upregulate the expression of EDC genes via AHR activation and maintain the healthy epidermal barrier. In line with this, the expression of FLG, LOR, and IVL is downregulated in keratinocytes with AHR knockdown or in the presence of AHR antagonists during the terminal differentiation of keratinocytes [79].…”
Section: Upregulation Of Ivl Lor and Flg By Ahr Activationmentioning
confidence: 99%
“…Consistent with this, long-lasting activation of AHR by dioxins induces the exaggerated terminal differentiation of keratinocytes and sebocytes, leading to the development of chloracne [27][28][29]. In particular, the exaggerated AHR activation converts sebocyte differentiation from sebaceous cell differentiation to keratinocytic differentiation, which results in the loss of sebocytes and keratinous The expression of EDC genes is not stable, but is actively modulated by external stimuli, including ultraviolet irradiation and photoproducts [14,15], dioxins, and other oxidative pollutants [4,16], bioproducts of commensal or symbiotic microorganisms such as Malassezia and Staphylococcus epidermidis [17][18][19], cosmetics [20], and various phytochemicals [21][22][23][24][25]. These chemical stimulants activate the xenobiotic chemical sensor aryl hydrocarbon receptor (AHR), upregulate the expression of barrier-related proteins, and accelerate the terminal differentiation of keratinocytes [4,14,16,18,26].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that M. pachydermatis is able to activate the aryl hydrocarbon receptor (AhR), a nuclear receptor and transcriptional regulator with pleiotropic effects that include down-regulation of immune stimulation, modification of melanogenesis and epidermal cell function, and inhibition of antagonistic microbes (Buommino et al, 2018). Since indole production was not detected in a study of 80 M. pachydermatis strains from canine otitis externa, AhR activation by M. pachydermatis might be associated with the release of compounds other than indolic metabolites (Kiss et al, 1996).…”
Section: Pathogenesis Of Malassezia Dermatitis In Dogs and Cats: Backmentioning
confidence: 99%